FILOSOFI MAHAR - Jaelani, Ahmad jelani; Zainal Arifin Haji Munir; Syukri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the lack of knowledge of some people regarding the meaning and significance of dowry, especially the general public. So that often occurs misunderstanding in marriage, such as some villagers believe that dowry is mandatory to be mentioned during the marriage contract, some believe that giving pisuke (Lombok tradition) is the same obligation as dowry, and there are still many more understandings and beliefs that need to be straightened out and explained thoroughly and precisely. So the purpose of this research is to explain and straighten out to the public about the meaning and significance, wisdom and purpose of dowry or bride price. So that will create a beautiful and religious Islamic marriage, the husband gives dowry with full sincerity and love, and the wife receives it with a smile and happiness, then become a couple full of blessings, and of course will be a longed for family, namely sakinah, mawasdah and rahmah (full of peace, love and affection).